The Three Versions of the Ultimatum Game: An Example from the History of Creation of the Kingdom of Serbs, Croats and Slovenes 1914-1918 - Dušan Pavlović; Stevo Đurašković (Anali Hrvatskog Politološkog Društva, 2021)
We examine the 1914-1918 creation of the Kingdom of Serbs, Croats and Slovenes as a form of the ultimatum game. The negotiations among the Serbian Cabinet and the Yugoslav Committee representatives of the Habsburg Souths Slavs from 1914-1918 exemplify three versions of this game. The first version is a typical (rational choice) type of the ultimatum game in which the Receiver is satisfied with any offer by the Proposer. The second version is an instance of behavioral game theory. When the Proposer gives an unfair offer, it provokes an emotional reaction in the Receiver who will reject it at the cost of harming themselves. We observe this behavior in the emotional behavior of Frano Supilo, a Croat and one of the leaders of the Yugoslav Committee. The third version of the behavioral ultimatum game can be observed in the behavior of Serbian Prime Minister Nikola Pašić who opposed any concessions to the Yugoslav Committee, thus giving an ultimatum to the Croat side to accept the Serbian offer or remain with nothing, which was harmful to the Serbian side, too. This example is important because it produces two conclusions. First, historical games are often a mixture of several versions. Second, Proposers, too, can have an emotional reaction and give an offer that can hurt themselves. This aspect of the ultimatum game is less mentioned because it is difficult to simulate in experiments.